2017
DOI: 10.1515/jpm-2015-0375
|View full text |Cite
|
Sign up to set email alerts
|

Is early breast milk fortification more effective in preterm infants?: a clinical trial

Abstract: Our findings suggest that early fortification from the first feeding in neonates with exclusive breast feeding did not improve growth in the first 4 weeks in preterm neonates in comparison with late fortification; so early fortification may not be cost effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…), duration of parenteral nutrition, growth at 34 weeks and bone mineral status throughout hospitalisation and description of nutritional intakes and growth outcomes between two cohorts after changes in practice . The authors of these studies consistently suggest that there is no increased risk of adverse effects with early fortification of human breast milk, although Tillman demonstrated a 32% lower risk of having the adverse event of blood in stools in the late fortification group, and both cases of necrotising enterocolitis (NEC) reported in the study conducted by Taheri et al . developed in infants receiving early fortification.…”
Section: Critical Appraisalmentioning
confidence: 99%
See 4 more Smart Citations
“…), duration of parenteral nutrition, growth at 34 weeks and bone mineral status throughout hospitalisation and description of nutritional intakes and growth outcomes between two cohorts after changes in practice . The authors of these studies consistently suggest that there is no increased risk of adverse effects with early fortification of human breast milk, although Tillman demonstrated a 32% lower risk of having the adverse event of blood in stools in the late fortification group, and both cases of necrotising enterocolitis (NEC) reported in the study conducted by Taheri et al . developed in infants receiving early fortification.…”
Section: Critical Appraisalmentioning
confidence: 99%
“…This systematic review did not identify any study that found a difference in growth outcomes or incidence of adverse events. Our study provides an updated review of the available literature, with two studies that we have identified being published after this review's literature searches were completed.…”
Section: Commentarymentioning
confidence: 99%
See 3 more Smart Citations